Germany's Post-1945 and Post-1989 Education Systems - Grimm, Sonja (World Bank, Washington, DC, 2017)
The re-education of the German people overseen by the victorious allied powers, the inclusion of the causes and consequences of totalitarianism in school curricula and a comprehensive policy of ensuring that the Nazi period remained firmly in the German collective memory were the elements that formed the basis of a viable liberal-democratic post-war consensus in West Germany. Democratic opinions and values progressively took the place of the racist, chauvinistic ideology of the National Socialists, which had proclaimed the superiority of the 'master race' and ultimately led to the outbreak of the Second World War. The most extensive re-education measures were implemented under the American occupation. The Office of Military Government for Germany US (OMGUS) under the US zone's Military Governor General Lucius D. Clay allocated $1.03 million to the education program in the period to 1948, while the amount increased to $48 million between 1949 and 1952 under the Office of the High Commissioner US, Germany (HICOG). In addition, by 1949 rehabilitation programs were already being undertaken in West Germany by more than 50 private American organizations, including the American Council on Education, the labor unions AFL and CIO, the League of Women Voters, and the Rockefeller and Ford Foundations (Rupieper 1996: 200).